Emotional Well-Being of Parents Undergoing Family Therapy in a Children's Psychiatric Clinic. (1st June 2022) - Dovbysh, D.; Bebchuk, M.; Kopytina, I.; Rodionova, A.; Maruk, I.; Balyakina, I.
Abstract : Introduction: Parents today can be important members of a multi-professional team, helping children with mental illness. The well-being of the parents is an important factor in successfully helping the child and willingness to cooperate with specialists. Objectives: To investigate the experiences of parents undergoing family psychotherapy on an outpatient basis and during a child's hospitalization. Methods: 86 parents who applied for family therapy on an outpatient basis and 80 parents (main group) of hospitalized children took part in the study. Participants were offered the following questionnaires: Beck Hopelessness Scale, modified scales of the Dembo-Rubinstein, GAD-7, PHQ-9, Quality of Life Enjoyment and Satisfaction Questionnaire. The study was conducted from 04/01/2021 to 04/14/2021. Results: The main group significantly differs from the outpatient group in the following parameters (according to the t-test): the level of depression (M=18, 34 and M=11, 61 respectively) and anxiety (M=12, 07 and M=7, 96 respectively), the quality of life in the sphere of emotional well-being, social sphere, activity and free time, as well as the happiness self-assessment scales. The results on the scales of depression and hopelessness are inversely significantly associated with the willingness of parents to participate in family psychotherapy (r=-0, 74, p=0, 01) visit the child (r=-0, 58, p=0, 05), and regularly contact a doctor (r=-0, 61, p=0, 05). Conclusions: Depending on the well-being of family members and the tasks facing the family, family assistance may differ depending on the stage of treatment of the child. Disclosure: No significant relationships.